Boosting Academic Performance With Adaptive Learning Strategies in Schools - Anggraeni, Wilis; Hidayah, Fathi; Aniati, Ana (FALASIFA : Jurnal Studi Keislaman, 2024)
This study focuses on implementing the semester credit system in the curriculum at madrasah and how this system can improve student learning achievement. The main objective of this study is to evaluate the effectiveness of the semester credit system in improving learning flexibility, individual skill development, student independence, and technology support. The research method used is a qualitative approach with a case study involving in-depth interviews with the principal, teachers, and students, classroom observation and document analysis. The study results indicate that the semester credit system improves curriculum flexibility, allows for adjustments to teaching materials according to student needs, and supports the development of student skills and independence. Technology support has also proven to be important in facilitating the implementation of this system and improving student learning experiences. The implications of this study emphasize the importance of implementing the semester credit system to improve academic performance and provide practical guidance for developing educational policies that are more responsive to student needs.